MACROPRUDENCIAL MANAGEMENT OF BANKING INSTITUTIONS DISTRESSED ASSETS - Shapoval, L.M.; Шаповал , Л.П.; Fuhelo, P.M. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The use of already known and the search for new effective macroprudential tools for managing the bank's distressed assets is a very important present issue. It requires in-depth study of the issue in the context of maintaining macroeconomic stability and preventing systemic risks accumulation in the banking system. Therefore, the purpose of the article is to summarize the theoretical and practical principles of macroprudential management of banking institutions. The necessity of introducing the early response system as an effective macroprudential tool for managing banking institutions distressed assets has been proved.During the research in order to assess problem state of non-performing loans and to clearly reflect its dynamics and structure, such general scientific methods were used as system method, complex method, analytical-statistical method, tabular-graphic method. The article presents the results of statistical material research which characterizes the main credit activity indicators of banks in Ukraine. Based on the comprehensive assessment of banks loan portfolio, the level of non-performing loans was determined, as well as the reasons of its occurrence. The introduction of an early response system in terms of effective management of bank troubled loans was justified. It should ensure the detection of potentially problematic assets at an early stage. The study suggests that the macro-prudential instruments introduced by the regulator to address the issue of minimizing the level of non-performing loans are in line with European best practices that based on the ECB Guidelines for Non-performing Loans, guidelines of the European Banking Authority for Unemployed and Restructured Exposures.